Digital planet tomorrow's technology and you - Beekman, George; Beekman, Ben (Pearson Education, 2014)
Today we're standing at the junction of three powerful and rapidly evolving technological forces: computers, communications, and digital entertainment. Computer technology is showing up in everything from automobiles to home appliances to telephones to televisions, and the lines that separate these machines are fading. This digital convergence is rapidly-and radically-altering the world in which we live.